The Role of Forensic Accounting in Fraud Detection and Prevention in Nigerian Public Sector: A Case Study of Lagos, Nigeria - Ogbaini, Aliu Clement; Akpor, Afam Augustine; Oboh, Ransome; Oputa, John Edewor; Marvis, Vine Bello (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study investigated the role of forensic accounting in fraud detection and prevention in the Nigerian Public Sector, Lagos State Government was used as a case study. The study aimed to assess the impact of forensic accounting on fraud detection and prevention in the Lagos State Government and recommend strategies for fraud prevention in the Nigerian Public Sector. A sample of 60 Certified Accountants was selected using purposive sampling techniques and secondary data from past financial statements. The findings were analyzed using frequency distribution tables, simple percentages and chi-square statistical formula. The findings of this study revealed that the Lagos State Government uses forensics minimally in its operations, with no forensic accounting department and no management training on forensic fraud prevention. The study calls for the government to go beyond annual and periodic audits and employ forensic accountants' services to regularly review all major financial transactions. There should be a separate office for forensic accountants at all government levels in Nigeria and regular management training on forensic fraud detection and prevention.